NEW GENERATIONS OF GAMES - INNOVATIVE GAMES (Proceedings of International Conference on Educational Discoveries and Humanities, 2022)
This paper introduces idea generation games designed for the use of game designers. Three games designed especially for generating new game ideas were developed in the GameSpace project that studies methods for design and evaluation of casual mobile multiplayer games. GameSpace idea generation games have been developed through an iterative process and in close cooperation with the end users, game industry professionals